Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Anyone can help with it.

Let $F:Set\to Set$ be given by $F(X)=H^S(X)\times S$. Let $\delta :H^S(X)\times S \to X$ be the evaluation map given by $\delta(p,s)=p(s)$, the value of the function p at the point s. How can we prove that $\delta$ is a natural transformation $F \Rightarrow 1_{Set} $.

share|cite|improve this question
what is $H^S(X)$ supposed to mean? – magma Jan 14 '14 at 17:28
up vote 4 down vote accepted

Let $H:\mathbf{Set}\to\mathbf{Set}$ denote the covariant hom functor $\text{Hom}(S,-)$, and $G$ the functor sending a map $k:Z\to Z'$ to the map $k\times\text{Id}:Z×S\to Z'×S$. Then your $F$ is just the composition $GH$ and this determines the arrow function of $F$. Now let $f:X\to X'$. The composition $$H(X)×S\xrightarrow\delta X\xrightarrow f X'$$ first maps a pair $(g,s)$ to the element $g(s)$, then to the element $f(g(s))$. On the other hand, the composition $$H(X)×S\xrightarrow{F(f)} H(X')×S\xrightarrow\delta X'$$ first sends the pair $(g,s)$ to the pair $(f\circ g,s)$, then evaluates this to $fg(s)$.

share|cite|improve this answer

By the definition. You already have a transformation $\delta\colon F\to I_{\mathbf{Set}}$, so you should only check naturality.

If I understood correctly, $F\colon\mathbf{Set}\to\mathbf{Set}$ is a functor, such that: $$ F(X)=X^S\times S;\qquad (F(f))(p,s)=(f\circ p,s). $$ The reason why I understood so is that the "standart" evaluation map in $\mathbf{Set}$ is a map $X^S\times S\to X$.

Let $f\colon X\to Y$ be a mapping, then we have to prove that $f\circ\delta(X)=\delta(Y)\circ F(f)$. Both $f\circ \delta(X)$ and $\delta(Y)\circ F(f)$ are mappings $X^S\times S\to Y$, therefore we should check that they coincide at any point $(p,s)\in X^S\times S$: $$ (f\circ \delta(X))(p,s)=f(\delta(X)(p,s))=f(p(s))=(f\circ p)(s)= $$

$$ =\delta(Y)(f\circ p,s)=\delta(Y)(F(f)(p,s))=(\delta(Y)\circ F(f))(p,s). $$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.